Thermoresponsive and biodegradable dextran based microgels: synthesis and structural investigation - Ghugare, Shivkumar V.; Chiessi, Ester; Sakai, Victoria Garcia; Telling, Mark T. F.; Wadgaonkar, Prakash P.; Paradossi, Gaio (Macromolecular Symposia, 2013)
Nanostructured objects, often ranging from hundreds of nanometers to few microns, support a number of functions directly linked to their structural features. They are, or they will be, protagonists in biomedical applications where miniaturized activities are required. These include the interface with living systems as tissues and cells, where targeted release of drug molecules occurs, or molecular imaging methods monitoring the drug trafficking in specific cell districts. The potentials of such devices, far to be fully understood, will be assessed only when a close correlation of their functions with their structure will be established. In this contribution we present a dextran based microdevice responsive to temperature and biodegradable. Both thermoresponsivity and biodegradability are of relevance for the potential use as drug carrier and controlled release device. The temperature behaviour, overall structure and internal architectures have been addressed with different methods.
Polymer Networks Conference (PNG), WY, AUG 12-16, 2012
Keywords: Biomaterials; colloids; dynamic light scattering; hydrogels; p(NiPAAm)